Implementasi Undang-Undang Nomor 5 Tahun 2014 Tentang Aparatur Sipil Negara Dalam Tindak Pidana Narkotika Berdasarkan Undang-Undang Nomor 35 Tahun 2009 Tentang Narkotika - Saepudin Saepudin (Jurnal Media Justitia Nusantara, 2018)
The crime of abuse of narcotics by civil servants is not only a serious violation of the State apparatus's disciplinary regulation but also a serious criminal offense, which should have been processed through the general court, but in fact there are some cases of criminal narcotics abuse whose punishment did not provide deterrent effect to other civil servants.This study aims to determine the implementation of Law Number 5 of 2014 concerning State Civil Apparatus to Civil Servants Who Conduct Criminal Acts, as well as legal actions that can be carried out by agencies against civil servants who are proven to commit criminal acts of narcotics abuse. The method used is descriptive analysis method with a normative juridical approach, analytical descriptive is research that describes applicable laws and regulations associated with legal theories and the practice of implementing positive law concerning issues. The results of this study indicate that the application of law to civil servants who commit narcotics crimes that is using legal remedies namely the perpetrators of narcotics crimes must be processed by law based on Law Number 35 of 2009 concerning Narcotics. While civil servants as criminal offenders are dishonorably discharged based on Article 87 of Law Number 5 of 2014 concerning State Civil Apparatus. Efforts to implement the law are carried out in a preventive manner, namely using legal remedies where perpetrators of narcotics crimes must be processed by law based on Law No. 35 of 2009 concerning narcotics. As for countermeasures so that other civil servants are not tempted to commit disciplinary violations, especially in narcotics crime violations, preventive measures are carried out in the form of prevention by conducting intensive guidance to civil servants by means of socialization and counseling about the dangers of narcotics and adverse impacts. from drug abuse.